Equivalence of Definitions of Hyperbolic Cotangent

From ProofWiki
Jump to navigation Jump to search

Theorem

The following definitions of the concept of Hyperbolic Cotangent are equivalent:

Definition 1

The hyperbolic cotangent function is defined on the complex numbers as:

$\coth: X \to \C$:
$\forall z \in X: \coth z := \dfrac {e^z + e^{-z} } {e^z - e^{-z}}$

where:

$X = \set {z : z \in \C, \ e^z - e^{-z} \ne 0}$

Definition 2

The hyperbolic cotangent function is defined on the complex numbers as:

$\coth: X \to \C$:
$\forall z \in X: \coth z := \dfrac {\cosh z} {\sinh z}$

where:

$\sinh$ is the hyperbolic sine
$\cosh$ is the hyperbolic cosine
$X = \set {z : z \in \C, \ \sinh z \ne 0}$

Definition 3

The hyperbolic cotangent function is defined on the complex numbers as:

$\coth: X \to \C$:
$\forall z \in X: \coth z := \dfrac {e^{2 z} + 1} {e^{2 z} - 1}$

where:

$X = \left\{{z : z \in \C, \ e^{2 z} - 1 \ne 0}\right\}$


Proof

\(\displaystyle \forall z \in \left\{ {z \in \C: \ e^{2 z} - 1 \ne 0}\right\}: \ \ \) \(\displaystyle \) \(\) \(\displaystyle \frac {e^{2 z} + 1} {e^{2 z} - 1}\) Definition of Hyperbolic Cotangent: Definition 3
\(\displaystyle \forall z \in \left\{ {z \in \C: \ e^z - e^{-z} \ne 0}\right\}: \ \ \) \(\displaystyle \) \(=\) \(\displaystyle \frac {e^z \left({e^z + e^{-z} }\right)} {e^z \left({e^z - e^{-z} }\right)}\)
\(\displaystyle \forall z \in \left\{ {z \in \C: \ e^z - e^{-z} \ne 0}\right\}: \ \ \) \(\displaystyle \) \(=\) \(\displaystyle \frac {e^z + e^{-z} } {e^z - e^{-z} }\) Definition of Hyperbolic Cotangent: Definition 1
\(\displaystyle \forall z \in \left\{ {z \in \C: \ \frac {e^z - e^{-z} } 2 \ne 0}\right\}: \ \ \) \(\displaystyle \) \(=\) \(\displaystyle \frac {\left({\dfrac {e^z + e^{-z} } 2}\right) } {\left({\dfrac {e^z - e^{-z} } 2}\right) }\)
\(\displaystyle \forall z \in \left\{ {z \in \C: \ \sinh z \ne 0}\right\}: \ \ \) \(\displaystyle \) \(=\) \(\displaystyle \frac {\cosh z} {\sinh z}\) Definition of Hyperbolic Cotangent: Definition 2

$\blacksquare$